The Effectiveness of Role-Playing Methods on Student’s Critical Thinking Skills in “Interaction Between Creatures And Its Surroundings” Topic in Junior Highschool 1 Berbah - Ainun Khuluqun Adzim (Universitas Negeri Yogyakarta, 2020)
The goal of This research are to understand the use role playing method impact on student’s critical thinking skills and the effectiveness of role playing method on students' critical thinking skills. This research is a quasi-experimental study using a non-equivalent control group research design. The population of this research is all of class VII of SMP Negeri 1 Berbah in academic year 2020/2021. The sampling technique in this study uses the Cluster Random Sampling method. By using the random sampling cluster technique, carrying out the class selection for the sample randomly, class D was obtained as experimental class and class C was obtained as the control class. The experiment class was using role-playing methods while the controlled class was using conventional methods. The data collection instrument consisted of pretest and posttest questions of critical thinking skills. The pretest-posttest score are used to obtain data for this study. The data analysis technique used are the prerequisite test in the form of normality and homogeneity tests and parametric statistical tests in the form of independent sample t-test, n-gain analysis and effect size. The results of this study showed that there is a significant effect in the use of role-playing methods on critical thinking skills of the students. From this study, it can be concluded that the role-playing methods are effective for the improvement of critical thinking ability of the students.